1974
DOI: 10.1113/jphysiol.1974.sp010488
|View full text |Cite
|
Sign up to set email alerts
|

The velocity of lymph flow in the canine thoracic duct

Abstract: SUMMARY1. The velocity and pattern of movement of lymph in the thoracic duct of anaesthetized and conscious dogs has been studied by observing the movement of droplets of ultrafluid lipiodol in the duct.2. The velocity of flow when anaesthetized varied from 0 1-2'0 cm/sec, to 5-0 cm/sec when conscious.3. The pattern of flow was affected by respiration and the cardiac cycle. Most movement occurred at the end of inspiration.4. The duct of five autopsy preparations was perfused with saline to assess the volume an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…In our study flow pulsation in the thoracic duct was completely independent of respiratory movements both in unanaesthetized and anaesthetized sheep. This finding is in apparent contrast to that of Browse et al (1974) and in part to that of Schad et al (1978). Both of these previous studies indicate a prominent or even dominant (Browse et al 1974) role of respiratory movements in anaesthetized dogs.…”
Section: Intrinsic and Extrinsic Factors In Propulsion Of Lymph In Thmentioning
confidence: 62%
See 3 more Smart Citations
“…In our study flow pulsation in the thoracic duct was completely independent of respiratory movements both in unanaesthetized and anaesthetized sheep. This finding is in apparent contrast to that of Browse et al (1974) and in part to that of Schad et al (1978). Both of these previous studies indicate a prominent or even dominant (Browse et al 1974) role of respiratory movements in anaesthetized dogs.…”
Section: Intrinsic and Extrinsic Factors In Propulsion Of Lymph In Thmentioning
confidence: 62%
“…This finding is in apparent contrast to that of Browse et al (1974) and in part to that of Schad et al (1978). Both of these previous studies indicate a prominent or even dominant (Browse et al 1974) role of respiratory movements in anaesthetized dogs. In two unanaesthetized dogs Browse et al (1974) observed a fast Lymph flow in intact thoracic duct Table 2.…”
Section: Intrinsic and Extrinsic Factors In Propulsion Of Lymph In Thmentioning
confidence: 62%
See 2 more Smart Citations
“…, Hangmyo CHO 1) , Haengbok CHEON 1) , Juhyung KIM 1) , Taehun KIM 1) , Ji-Houn KANG 1) , Gonhyung KIM 1) , Youngwon LEE 2) , Hojung CHOI 2) , Heechun LEE 3) and Dongwoo CHANG 2) Chylothorax is a condition characterized by accumulation of a fluid containing chylomicrons in the pleural cavity. Lymphography is essential for evaluating the integrity of the thoracic duct and its branches, and several techniques, including pedal lymphography, and direct mesenteric lymphangiography, have been used to identify the causes of chylothorax in dogs.…”
mentioning
confidence: 99%